2017
DOI: 10.1155/2017/5950395
|View full text |Cite
|
Sign up to set email alerts
|

Different Modulatory Effects of IL-17, IL-22, and IL-23 on Osteoblast Differentiation

Abstract: Objectives To examine the expressions of IL-17, IL-22, and IL-23 receptors in four osteoblast models and the effects of IL-17, IL-22, and IL-23 on osteoblasts. Methods Gene expression levels of receptors, alkaline phosphatase (ALP), osteocalcin (OCN), and Runt-related transcription factor 2 (Runx-2), were evaluated by RT-PCR and real-time RT-PCR. Proliferative responses and cell cycle analysis were detected by a CCK-8 assay and flow cytometry, respectively. ALP activity and ALP mass were detected by an ALP act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…Recent efforts have focused on elucidating the mechanisms behind these effects and indicate that IL-17A stimulates receptor activator of nuclear factor-kB ligand (RANKL) expression and inhibition of Wnt signalling, thereby inhibiting osteoblast activity (figure 3). 122–128…”
Section: Role Of Il-17a In Spamentioning
confidence: 99%
“…Recent efforts have focused on elucidating the mechanisms behind these effects and indicate that IL-17A stimulates receptor activator of nuclear factor-kB ligand (RANKL) expression and inhibition of Wnt signalling, thereby inhibiting osteoblast activity (figure 3). 122–128…”
Section: Role Of Il-17a In Spamentioning
confidence: 99%
“…(14,15) Furthermore, IL17A has been reported to inhibit osteoblastogenesis. (125)(126)(127) IL17A has also been shown to induce Lcn2 in several cell types in vitro andin vivo. (124,(128)(129)(130)(131) Therefore, SFB-induced IL17A productionin thegut may stimulate hepatic LCN2 synthesis and increased circulating levels of LCN2.…”
Section: Discussionmentioning
confidence: 99%
“…IL17A signaling in stromal/osteoblastic cells critically regulates proinflammatory/pro‐osteoclastic cytokine expression, and CD4 + T H 17 cell‐derived IL17A can have catabolic actions via signaling at stromal/osteoblastic cells . Furthermore, IL17A has been reported to inhibit osteoblastogenesis . IL17A has also been shown to induce Lcn2 in several cell types in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Kamiya et al [19] reported that no remarkable changes were observed in the expression of mRNA for type I collagen or ALP in osteoblasts after stimulation by IL-23, indicating that IL-23 had no direct actions on osteoblasts. We con-firmed that IL-23 had no direct effects on osteoblasts, since osteoblasts marginally express IL-23 receptors [20]. Taken together, the above data imply that IL-23 indirectly induces new bone formation at the sites of entheseal inflammation.…”
Section: Introductionmentioning
confidence: 52%